Answer:
Explanation:
1 Solve:
8r + 4 = 10 + 2r
We will collect the variable terms on the left hand side of the equation and constants on the right hand side of the equation
8r - 2r = 10-4
6r = 6
r= 6/6 = 1
2 Solve:
-2(x + 3) = 4x - 3
-2x -6 = 4x - 3
We will collect the variable terms on the left hand side of the equation and constants on the right hand side of the equation
-2x - 4x = -3 + 6
-6x = 3
x = 3/-6
x = -1/2
3 Solve
5 + 3(q - 4) = 2(q + 1)
5 + 3q - 12= 2q+2
We will collect the variable terms on the left hand side of the equation and constants on the right hand side of the equation
3q - 2q = 2 +12 - 5
q = 9
4. Solve
7x - 4 = -2x + 1 + 9x - 5
We will collect the variable terms on the left hand side of the equation and constants on the right hand side of the equation
7x +2x-9x = 1 - 5 +4
0= 0
5 Solve:
8x + 6 - 9x = 2 - x -15
We will collect the variable terms on the left hand side of the equation and constants on the right hand side of the equation
8x -9x + x = 2 - 15 -6
0x = -19
0= 19